Impact of Tube Voltage on Radiation Dose (CTDI) and Image Quality at Chest CT Examination - M. El Mansouri; A. Choukri; M. Talbi; O. K. Hakam (PPIKSN-BATAN, 2021)
During Computed Tomography (CT) scan examinations, it is important to ensure a good diagnosis by providing the maximum information to detect pathologies and this can be done with a reduced dose. In this respect, several methods of dose reduction have been studied and evaluated. This work investigates the effect of tube voltage while varying the tube current on image quality and radiation dose at Chest CT examination. This study was conducted on HITACHI CT 16 slice Scanner using two phantoms for evaluating the dose and image quality; a PMMA phantom and a CATPHAN 500. Two tube voltages of 120 KVp and 100 KVp have been used for some variation of the tube currents (mAs) and recording the values of the measured quantities (CTDIv, spatial resolution, contrast to noise ratio CNR and noise). The scanning with 100 KVp at Chest CT examination led to a reduction in CTDIv until 45 %, an increase of noise from 17 % to 45 %, and the Spatial Resolution fell slightly (6 and 7 pl/cm) compared to the 120 KVp. The CNR shows a slight regression from 11 to 22 % for the 120 KVp and 100 KVp. This study has shown that despite the increase in the image noise at low tube voltage 100 KVp, it is possible to reduce the radiation dose by up to 45 % without degradation of image quality at Chest CT examination. Further works will evaluate the effect of acquisition parameters in other CT examinations.